Virtual Realism: David Chalmers on the Ontological Status of Virtual Reality - Sulaiman, Ahmad; Fauzi, Ammar (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2025)
The presence of a new technology can bring a novel perspective which then reopens old philosophical questions. Virtual reality, for example, recycles passion in the West over metaphysical topics. Fundamental questions regarding reality are coming back to life and attracting heated philosophical debates such as: How to define reality? What is the limit or scope of reality? Can we really reach or know true reality? David Chalmers, an Australian-American techno-philosopher, is a figure at the center of this field of study. He presents the concept of “virtual realism” to represent the view that all objects and environments in virtual reality are real and equal to everything else. This raises the question of how we should interpret all objects, actions, experiences and events in virtual reality and their relationship to non-virtual reality. The purpose of this research is to elaborate and analyze virtual realism as conceptualized by Chalmers. This research conducted a conceptual study to understand the arguments and theses put forward by Chalmers. The results of the research show that Chalmers constructed virtual realism using various realism arguments eclectically. Chalmers' ultimate argument says that as in non-virtual reality, there is also a degree of power and causality in virtual circumstances that can both influence and influence non-virtual reality.